2020
DOI: 10.48550/arxiv.2012.10309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning Contextual Representations for Semantic Parsing with Generation-Augmented Pre-Training

Abstract: Most recently, there has been significant interest in learning contextual representations for various NLP tasks, by leveraging large scale text corpora to train large neural language models with self-supervised learning objectives, such as Masked Language Model (MLM). However, based on a pilot study, we observe three issues of existing general-purpose language models when they are applied to text-to-SQL semantic parsers: fail to detect column mentions in the utterances, fail to infer column mentions from cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Based on the results, we find that using the generated question as text input is a better choice than these two proposals, thus we did not use them in our main experiments. (Herzig et al 2020;Eisenschlos, Krichene, and Müller 2020;Shi et al 2020;Deng et al 2020;Yin et al 2020;Yu et al 2020;Iida et al 2021;Liu et al 2021). Large scale crawled tables are used for pretraining to enhance the table representation ability of language models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results, we find that using the generated question as text input is a better choice than these two proposals, thus we did not use them in our main experiments. (Herzig et al 2020;Eisenschlos, Krichene, and Müller 2020;Shi et al 2020;Deng et al 2020;Yin et al 2020;Yu et al 2020;Iida et al 2021;Liu et al 2021). Large scale crawled tables are used for pretraining to enhance the table representation ability of language models.…”
Section: Resultsmentioning
confidence: 99%
“…However, this causes a mismatch between the intermediate pre-training and downstream tasks where questions are one essential component of the tasks. More recently, Shi et al (2020) confirmed that the surrounding text is far from optimal because those texts are dissimilar to the natural language questions in terms of text length, composition and content. The surrounding text of the tables can be quite noisy and may be irrelevant to the tables.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Methods like TAPAS [38] and TaPEx [69] [94] encodes tables with a tabular graph transformer, contexts with a BERT-based model [30], and queries with a FastText method [57], and calculates the relevance score of the query-table and query-context matching by multi-layer perceptron (MLP). [29], GraPPa [105], GAP [81] promote semantic parsing through pre-training on synthetic or human-labeled table-text data.…”
Section: Table Factmentioning
confidence: 99%
“…The current state-of-the-art on SPIDER [32] dataset are PICARD [24] and SADGA [6]. SADGA is built on pretrained GAP [25] model which is in turn a modification of RAT-SQL [28] framework. While PICARD [24] is a text-to-SQL semantic parser built upon pre-trained encoder-decoder models.…”
Section: Related Workmentioning
confidence: 99%